An Uncommon Case of Plasma Cell Mucositis of the Tongue in a Young Man - Alessandro Antonelli; Fiorella Averta; Federica Diodati; Danila Muraca; Ylenia Brancaccio; Chiara Mignogna; Amerigo Giudice (Case Reports in Dentistry)
Plasma cell mucositis (PCM) is an unusual plasma cell proliferative disorder of the upper aerodigestive tract. It is a rare disease, and its etiology is not yet known with variable clinical features. Symptoms include dysphagia, oral pain, and swelling. We described a case of PCM involving the tongue of a 14-year-old man. In the first place, several diagnostic hypotheses were proposed, most of them discarded for incompatibility with blood and laboratory tests. This disease rarely manifests itself on the tongue, especially in young patients with no comorbidities. The management of PCM is mainly aimed at reducing the symptoms, and in our report, the treatment involved the use of systemic prednisone with an improvement of the quality of life. At 1-year follow-up, there was no recurrence of the disease. Many therapeutic treatments are able to stabilize but not able to induce a complete remission. PCM is considered an uncommon benign disorder with a favorable prognosis and should be considered in the differential diagnosis with other inflammatory or neoplastic conditions.